Reinforced thermoplastic composites with interfacial microarchitectural anchoring: Computational study. (1st May 2017) - Ozsoy, Istemi B.; Choi, Hongseok; Joseph, Paul; Li, Gang; Luzinov, Igor; Zhao, Huijuan
Graphical abstract: Abstract: Reinforcing potential of fibers is limited for a number of thermoplastic polymers due to the inherently weak interfacial bonding between the non-polar/non-reactive polymer matrix and fiber surface. To this end, the concept of enhancing the interfacial strength in thermoplastic composites via controlled mechanical interlocking between fiber surface and polymer matrix is explored. Specifically, infiltration of the thermoplastic polymer into the anchoring sites around the microstructures located on the fiber surface provided an efficient mechanical interlocking. A computational study has been performed for several different surface morphologies for a glass/polyethylene material system. The strength calculations addressed both material failure and detachment of the matrix material from the anchoring sites. The results obtained, which focused on shear loading, indicated that the surface morphology has a significant effect on the interfacial bonding strength. The computational analysis results showed that even without any interfacial friction or adhesion, the interface strength could achieve 50% of the theoretical strength of perfect matrix-fiber bonding for a plane interface. An optimal geometry and density of the microarchitectured features on the surface was identified for many cases in a parametric study. Friction at the interface between polymer matrix and fiber surface was shown to provide a significant increase in interfacial strength for cases where the frictionless case detached, but not for cases of material failure, which shows the promise of anchoring when friction and adhesion cannot be relied on. It was therefore demonstrated that the precise surface morphology modification is an effective approach to improve the interfacial bonding in fiber reinforced thermoplastic composites.